Construction of a Utopian West: The Russian Nineteenth-Century Intelligentsia. (13th May 2014) - Shlapentokh, Dmitry
<x content-type="archive" xml:space="preserve">Abstract</x> A person's image of a foreign country is often not related to an actual encounter, but limited and one-sided based on the environment of the person's native land. Consider, for example, the Russian elite perception of the West in the eighteenth and early nineteenth centuries. Peter the Great's reign shook Russia's traditional society and led to the spread of promiscuity and general immorality. Consequently, for many Russians, whether or not they traveled, the West, epitomized by France, was a place of erotic pleasures and easygoing life. By the beginning of the nineteenth century some members of the Russian elite started to question the political system of their native land. For some of them, like Peter Chaadaev, the West stood as a symbol of the ideal political institutions and Russia for the dead end of history.